BASALT FIBERS AND MECHANICAL PROPERTIES OF BASALT FIBER REINFORCED CONCRETE - Kizilkanat, Ahmet B.; Kabay, Nihat; Akyucnu, Veysel; Erdogan, Gokhan (YILDIZ TECHNICAL UNIV, 2014)
Concrete is a brittle material with a low energy absorption capacity. There are several methods to increase the ductility of concrete where incorporation of different type of fibers is usually known as the most effective one. The most common type of fibers used for reinforcing concrete is steel, polymer, glass and carbon fibers. Although the addition of fibers might slightly increase the compressive strength of concrete, the main benefit occurs in terms of flexural and tensile strength of concrete. The principal role of the fibers is to modify the behavior of the material once the concrete matrix has cracked by bridging across the cracks as they begin to open and preventing the crack development. Basalt fibers are obtained by melting process of volcanic basalt rock. These fibers have many superior properties when compared to other fibers. Studies have shown that basalt fibers favorably affect the mechanical properties of concrete such as tensile strength and fracture energy.
Keywords: Basalt fibers; concrete; durability; mechanical properties; TOUGHNESS; Engineering